PENDAPATAN USAHA TANI AGROFORESTRI TRADISIONAL PADA BEBERAPA KEMIRINGAN LAHAN DI KELURAHAN KINALI KABUPATEN MINAHASA - Mildsty Tarore; Semuel P. Ratag; Hengki D. Walangitan; Euis F.S. Pangemanan (COCOS, 2015)
ABSTRACTTHE FARMING BUSINESS INCOME OF TRADITIONAL AGROFORESTRY ON SOME SLOPE AT KINALI VILLAGE-MINAHASA REGENCYThis research aims to analyze the farmer’s income of agro-forestry farmland based on slope declivity. This research was run on May-June 2014 at Kinali Village Kawangkoan Sub-regency Minahasa regency. The Method was used in this research was purpossive, 10 units of farmlands were chosen based on three cluster of slope. They were 0-15 degrees, >15-30 degrees and >30 degrees. The implementation of traditional agroforesrty system in Kinali village give higher income to farmer than monoculture system. The income from seasonal plants give contribution from Rp. 1.000.000,- to Rp. 3.000.000,- per planting season. Besides contribution of woody plants income are from Rp. 2.000.000 to Rp. 118.785.000. The income from woody plants is potential value based from stumpage value that grow there.Key words; farming business income, agro-forestry, Kinali Village, slope